Prenatal Cocaine Disrupts Serotonin Signaling-Dependent Behaviors:Implications for Sex Differences, Early Stress and Prenatal SSRI Exposure - K. Williams, Sarah; M. Lauder, Jean; M. Johns, Josephine (Current Neuropharmacology, 2011)
Prenatal cocaine (PC) exposure negatively impacts the developing nervous system, including numerous changes in serotonergic signaling. Cocaine, a competitive antagonist of the serotonin transporter, similar to selective serotonin reuptake inhibitors (SSRIs), also blocks dopamine and norepinephrine transporters, leaving the direct mechanism through which cocaine disrupts the developing serotonin system unclear. In order to understand the role of the serotonin transporter in cocaine's effect on the serotonergic system, we compare reports concerning PC and prenatal antidepressant exposure and conclude that PC exposure affects many facets of serotonergic signaling (serotonin levels, receptors, transporters) and that these effects differ significantly from what is observed following prenatal SSRI exposure. Alterations in serotonergic signaling are dependent on timing of exposure, test regimens, and sex. Following PC exposure, behavioral disturbances are observed in attention, emotional behavior and stress response, aggression, social behavior, communication, and like changes in serotonergic signaling, these effects depend on sex, age and developmental exposure. Vulnerability to the effects of PC exposure can be mediated by several factors, including allelic variance in serotonergic signaling genes, being male (although fewer studies have investigated female offspring), and experiencing the adverse early environments that are commonly coincident with maternal drug use. Early environmental stress results in disruptions in serotonergic signaling analogous to those observed with PC exposure and these may interact to produce greater behavioral effects observed in children of drug-abusing mothers. We conclude that based on past evidence, future studies should put a greater emphasis on including females and monitoring environmental factors when studying the impact of PC exposure.
Keywords: prenatal antidepressants